Meningkatkan Hasil Belajar PJOK Materi Bola Kaki Peserta Didik dengan Penggunaan Metode Daring di Kelas V SDN 47 Payakumbuh Semester 1 T.P 2021/2022 - Akhirman Thias (Departement of Mathematics Education, 2022)
This study aims to see and analyze the use of the online method to improve PJOK learning outcomes for students in foot ball material for students in the subject matter of soccer games in class V SDN 47 Payakumbuh Semester I TP. 2021/2022. This research was conducted using the Classroom Action Research method which consisted of three cycles, where each cycle consisted of; planning, action, observation and reflection. It will be held from July to December 2021. Data is processed in each cycle and then analyzed using percentages. The results obtained from this study are that using the online method can improve student learning outcomes. This is evident from the increase in student learning outcomes in each cycle, on the value of knowledge and skills. The conclusion obtained from this study is that the use of the Online Method can improve students' PJOK learning outcomes.